Microeconometrics using Stata - Cameron, A. Colin (Adrian Colin); Trivedi, P. K. (Stata Press, 2022)
"Microeconometrics Using Strata, Second Edition is aimed at both students and researchers of economics and related social science. The first volume is intended to be a self-contained treatment that might also be used as an applied econometrics course text. It focuses on the linear regression model and includes instrumental-variables estimation, random- and fixed-effects models, quantile regression, and analytical and bootstrap inference. It additionally provides a brief introduction to nonlinear regression models. The second volume covers models for binary, multinomial, censored, duration, and count outcomes for both cross-sectional and panel datasets. It then covers causal methods for exogenous and endogenous treatment evaluations, spatial regression, semiparametric methods, machine learning for prediction and for causal inference, and Bayesian methods"--